PENINGKATAN KINERJA SUMBER DAYA MANUSIA MELALUI INISIATIF DAN ORIENTASI PEMBELAJARAN SERTA KEMAMPUAN PENYESUAIAN - Wulan Asih (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2017)
The purpose of this study is to describe and analyze the influence of initiative, learningorientation, adaptability to HR performance. Data obtained from HR nurses in RSUD DR. R.Soedjati Soemodiardjo Purwodadi Grobogan using the questionnaires of 96 respondents. Thesampling technique non probability sampling method. Data analysis method used is multiplelinier regression. Results from this study showed that the variables of initiative and learningorientation has a significant effect on adaptability. Learning orientation and adaptability hasa significant effect on HR performance. While of initiative is not a significant effect on HRperformance. The results show that adaptability is not able to become an intervening variablebetween initiative influence on HR performance and adaptability is not able to become anintervening variable between learning orientation influence on HR performance.Keywords : Initiative, Learning Orientation, Adaptability, and HR performance.